A fraud detection model: A must for auditors - Krambia-Kapardis, Maria (My University, 2002)
This paper addresses a fundamental issue in financial regulation - that of the auditor’s ability to detect material irregularities. If an auditor is to detect irregularities he/she must also be cognisant of fraud aetiology by drawing on such other disciplines as psychology, criminology and sociology. The paper first provides a critique of existing fraud aetiology models and then describes the ROP Fraud Risk-Assessment Model constructed by the author in a study of convicted serious fraud offenders in Australia. The main concern of the paper is with the eclectic fraud detection model (EFD), of which the ROP model is a component. The EFD model is aimed at enhancing the auditor’s fraud detection ability, it has been constructed by the author and its utility successfully tested in Australia in a survey of auditors. Finally, the policy implications for auditors of the findings obtained are also considered.
Keywords: Auditors; Australia; EFD model; Fraud detection; Auditors; Australia; EFD model; Fraud detection